High efficient separation of H2/CH4 using ZIF-8/glycol-water slurry: Process modelling and multi-objective optimization. (29th April 2023) - Peng, Xiaowan; Zhang, Ruihang; Wang, Zexin; Deng, Chun; Liu, Bei; Yang, Mingke; Dong, Baocan; Li, Rui; Peng, Yun-Lei; Sun, Changyu; Chen, Guangjin
Abstract: Hydrogen (H2 ) is expected to play a vital role in future global energy system. The efficient and low-energy consumption process for H2 /CH4 separation from hydrogen rich industrial off-gas is still a key challenge. The absorption-adsorption process for H2 /CH4 separation using ZIF-8/glycol-water slurry is a promising alternative technique due to its high separation efficiency, mild operation conditions and continuous operation mode. We proposed two process configurations: a decompression desorption process A to obtain 99.5 mol% H2 ; and a process B combined with decompression and H2 stripping desorption to attain 99.99 mol% H2 . The detailed process modelling and multiple objective optimizations for two processes are conducted to determine optimal operation conditions, stream characteristics, and unit energy requirements. Results show that the H2 recovery ratio and total unit energy consumption reaches 99.70% and 0.3876 kW·h/Nm 3 for Process A; 99.47% and 0.4608 kW·h/Nm 3 for Process B, respectively. It indicates the novel process can simultaneously achieve high purity and high H2 recovery with low energy consumption. Graphical abstract: Image 1 Highlights: Absorption-adsorption process via ZIF-8 slurry is a promising alternative for CH4 /H2 separation. Two processes were proposed to produce H2 with different purities (99.5 mol% and 99.99 mol%). Multi-objective optimization provides the trade-off between H2 recovery and energy consumption. High-purity H2 can be produced with high recovery ratio (99.47%) and low energy penalty (0.4608 kW·h/Nm 3 ).